The Glycosylation Site of Myelin Oligodendrocyte Glycoprotein Affects Autoantibody Recognition in a Large Proportion of Patients - Marti Fernandez, Iris; Macrini, Caterina; Krumbholz, Markus; Hensbergen, Paul J.; Hipgrave Ederveen, Agnes L.; Winklmeier, Stephan; Vural, Atay; Kurne, Asli; Jenne, Dieter; Kamp, Frits; Gerdes, Lisa Ann; Hohlfeld, Reinhard; et al. (Frontiers in Immunology, 2019)
Autoantibodies to myelin oligodendrocytes glycoprotein (MOG) are found in a fraction of patients with inflammatory demyelination and are detected with MOG-transfected cells. While the prototype anti-MOG mAb 8-18C5 and polyclonal anti-MOG responses from different mouse strains largely recognize the FG loop of MOG, the human anti-MOG response is more heterogeneous and human MOG-Abs recognizing different epitopes were found to be pathogenic. The aim of this study was to get further insight into details of antigen-recognition by human MOG-Abs focusing on the impact of glycosylation. MOG has one known N-glycosylation site at N31 located in the BC loop linking two beta-sheets. We compared the reactivity to wild type MOG with that towards two different mutants in which the neutral asparagine of N31 was mutated to negatively charged aspartate or to the neutral alanine. We found that around 60 % of all patients (16/27) showed an altered reactivity to one or both of the mutations. We noted 7 different patterns of recognition of the two glycosylation-deficient mutants by different patients. The introduced negative charge at N31 enhanced recognition in some, but reduced recognition in other patients. In 7/27 patients the neutral glycosylation-deficient mutant was recognized stronger. The folding of the extracellular domain of MOG with the formation of beta-sheets did not depend on its glycosylation as seen by circular dichroism. We determined the glycan structure of MOG produced in HEK cells by mass spectrometry. The most abundant glycoforms of MOG expressed in HEK cells are diantennary, contain a core fucose, an antennary fucose and are decorated with α2,6 linked Neu5Ac, while details of the glycoforms of MOG in myelin remain to be identified. Together, we (1) increase the knowledge about heterogeneity of human autoantibodies to MOG, (2) show that the BC loop affects recognition in about 60 % of the patients, (3) report that all patients recognized the unglycosylated protein backbone, while (4) in about 20 % of the patients the attached sugar reduces autoantibody binding presumably via steric hindrance. Thus, a neutral glycosylation-deficient mutant of MOG might enhance the sensitivity to identify MOG-Abs.